DESCRIPTION OF QUALITATIVE WORKLOAD, CAREER DEVELOPMENT AND PERSONAL RESPONSIBILITY TOWARD THE RISK OF WORK STRESS OPERATORS ON AIR TRAFFIC CONTROLLER (ATC) - Fatmawaty Mallapiang; Ayu Hamid; Hasbi Ibrahim; Azriful Azriful (Universitas Islam Negeri Alauddin Makassar, 2022)
Background:operator Air Traffic Controller (ATC) or air traffic guide is a job that is responsible for flight safety so that the aircraft can fly safely without any aircraft accidents from departing to arriving at the destination, which is at risk of experiencing work stress.Objective: This study aims to describe the qualitative workload, career development and personal responsibility for the risk of work stress on ATC operators. This type of research is quantitative with a descriptive approach.Methods:The population in this study were all ATC operators at Sultan Hasanuddin International Airport Makassar as many as 67 people. Sampling was carried out using themethod Total Sampling of 67 respondents. Measurement of Work Stress using a questionnaire instrument Stress Diagnosis Survey (SDS).Results:The results showed that ATC operators experienced moderate work stress as much as 52.2%, qualitative workload in the medium category by 71.6%, career development in the moderate category as much as 59.7% and personal responsibility in the moderate category by 53.7%.Conclusion:ConclusionQualitative workload, career development, and personal responsibility of ATC operators are all in the medium category, most of them experience moderate work stress, especially the Tower work unit, and the dominant work stress risk factor is qualitative workload.It is recommended thatmanagement should routinely conduct training related to ATC so that operator skills are updated according toneeds ofthethe independent variables are not related to student stress levels.